2007
DOI: 10.1158/1078-0432.ccr-06-1753
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of BRAF/MEK/MAP Kinase Pathway Restores Expression of Iodide-Metabolizing Genes in Thyroid Cells Expressing the V600E BRAF Mutant

Abstract: Purpose: The V600E BRAF mutant plays an important role in the pathogenesis of papillary thyroid cancer (PTC) and is associated with loss of expression of thyroid iodide-metabolizing genes. This study was done to investigate the restorability of expression of these genes by suppressing the BRAF/extracellular signal-regulated kinase kinase (MEK)/mitogen-activated protein (MAP) kinase pathway in V600E BRAF^harboring thyroid cells and to explore the mechanisms involved. Experimental Design: We used inducible expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
113
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 32 publications
(28 reference statements)
8
113
1
2
Order By: Relevance
“…Interestingly, several thyroid-specific genes were shown to be silenced on activation of the BRAF=MAPK=MEK pathway, with induced expression of BRAF V600E in rat thyroid cell line PCCL3 (48,49). Suppression of MAPK pathway could restore the expression of these genes.…”
Section: Epigenetic Alterations In Thyroid Cancer and Related Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, several thyroid-specific genes were shown to be silenced on activation of the BRAF=MAPK=MEK pathway, with induced expression of BRAF V600E in rat thyroid cell line PCCL3 (48,49). Suppression of MAPK pathway could restore the expression of these genes.…”
Section: Epigenetic Alterations In Thyroid Cancer and Related Cell Linesmentioning
confidence: 99%
“…Suppression of MAPK pathway could restore the expression of these genes. In case of TSH-R gene, demethylation of the gene associated with its expression occurred with suppression of the BRAF=MAPK=MEK pathway (49). Although the tumorigenic role of these genes is not clear, the silencing of these thyroid-specific genes by methylation can cause failure of clinical radioiodine treatment of thyroid cancer.…”
Section: Epigenetic Alterations In Thyroid Cancer and Related Cell Linesmentioning
confidence: 99%
“…Indeed, suppression of the MAPK pathway by knockdown of mutant BRAF or administration of the MEK inhibitor restores expression of iodide-metabolizing genes in human thyroid carcinoma cells expressing the BRAF mutation. 29 It is likely that endogenous epigenetic genes, such as DNA methyl transferases (DNMTs) and HDACs, mediate Epigenetic silencing of TTF-1 in thyroid T Kondo et al epigenetic dysregulation of tumor-suppressor genes in carcinoma cells. 30 Overexpression of DNMT1 and HDACs has been described in several human cancers including colorectal and breast cancers.…”
Section: Restoration Of Ttf-1 By Epigenetic Modifiersmentioning
confidence: 99%
“…In vitro studies have shown that expression of RET/PTC (De Vita et al 1998 or BRAF V600E (Mitsutake et al 2005, Liu et al 2007) in PCCl3 rat thyroid cells leads to a down-regulation of expression of thyroid-specific genes. A higher level of expression of matrix-metalloproteases and a higher cell motility have been found in BRAF V600E -expressing cells as compared with RET/PTC3-expressing PCCl3 cells (Mesa et al 2006).…”
Section: Introductionmentioning
confidence: 99%